Emerging natural and tailored perovskite-type mixed oxides–based catalysts for CO2 conversions - Wu, Juan; Ye, Runping; Xu, Dong-Jie; Wan, Lingzhong; Reina, Tomas Ramirez; Sun, Hui; Ni, Ying; Zhou, Zhang-Feng; Deng, Xiaonan (Frontiers in Chemistry, 2022)
The rapid economy and society development has led to unprecedent energy demand and consumption resulting in harmful emission of pollutants. Hence, conversion of greenhouse gases into valuable chemicals and fuels has become an urgent challenge for the scientific community. In recent decades, perovskite-type mixed oxide based catalysts have attracted significant attention as efficient CO2 conversion catalysts due to the characteristics of both reversible oxygen storage capacity and stable structure compared to traditional oxide-supported catalysts. In this review, we hand over a comprehensive overview of the research for CO2 conversion by these emerging perovskite-type mixed oxide based catalysts. Three main CO2 conversions, namely reverse water gas shift reaction, CO2 methanation, and CO2 reforming of methane have been introduced over perovskite-type mixed oxide based catalysts and their reaction mechanisms. Different approaches for promoting activity and resisting carbon deposition have also been discussed, involving increased oxygen vacancies, enhanced dispersion of active metal, and fine-tuning strong metal-support interactions. Finally, the current challenges are mooted, and we propose future research prospects in this field to inspire more sensational breakthroughs in the material and environment fields.